Secuencias de 658 pares de bases (fragmento barcode) del gen citocromo c oxidasa subunidad I (COI) de Evandromyia cortelezzii y Migonemyia migonei de Córdoba, Argentina - Laurito, Magdalena (2023)
Sand fly identification is complex because it depends on the expertise of the taxonomist. The females show subtle morphological differences and the occurrence of the species complexes are usual in this taxon. Therefore, a fragment of the cytochrome c oxidase subunit I (COI) gene is used for taxon barcoding to resolve this kind of problem. This study incorporates barcode sequences, for the first time, for Evandromyia cortelezzii and Migonemyia migonei from Argentina. The nucleotide sequence divergences were estimated to generate a neighbour-joining (NJ) tree. The automatic barcode gap discovery (ABGD) approach was employed to find the barcode gaps and the operational taxonomic unit (OTU) delimitation. Other species of the subtribe were included. The frequency histogram of divergences showed a barcoding gap. The ABGD analysis identified 14 operational taxonomic units (OTUs) from 13 morphological species. Sequences of Ev. cortelezzii and Mg. migonei formed well supported clusters and were diagnosed as primary species. These sequences are useful tools for molecular identification of the sand flies of the New World.